The analysis of liquidity and profitability ratios to assess financial distress potential in the balken wood business in Piabung Village - Widiarti Widiarti; Selly Puspita Sari (Institute of Accounting Research and Novation (IARN), 2025)
This study aims to analyse liquidity and profitability ratios in assessing the potential for financial distress in the balken wood business in Piabung Village. The main urgency faced by the business is the slow turnover of receivables, which disrupts cash flow and threatens business continuity. This research employs a qualitative descriptive approach using a case study method. Data collection techniques include basic financial documentation and semi-structured interviews with three key informants: the business owner and two administrative staff. Data analysis is conducted using Miles and Huberman's interactive model, which involves data reduction, data display, and conclusion drawing. The results show that the business lacks an understanding of the importance of financial ratios and does not maintain formal financial statements. The business’s cash flow heavily depends on receivable payments, so delays from customers result in difficulties meeting obligations to third parties, including banks. Nevertheless, the business manages to remain profitable by minimizing operational costs and adjusting production volume. The main strategies to address financial distress include accelerating receivable collection, maintaining communication with banks, and implementing strict cash management. The findings highlight the importance of improving financial literacy and adopting simple bookkeeping systems to help small businesses manage finances and anticipate financial distress more effectively.